The use of English amongst urban Malayalee youths in Seremban / Krishnan Ramoo - Krishnan , Ramoo (2017)

(untitled)
The purpose of this research is to study English usage amongst Malayalee youths between the ages of 17 and 24. This study focused on the language preference of youths when they communicate with other Malayalees in different domains. The researcher used mixed methods that employed the questionnaire as an instrument for the collection of quantitative data. Semi-structured interviews and a focus group discussion for qualitative data were also carried out to elicit qualitative data on their use of English and their perception towards their own mother tongue, Malayalam. The study was also aimed to investigate what these youths considered to be their identity markers as Malayalees. The results showed that on the whole, Malayalee youths preferred English compared to Malayalam in most domains selected for this study. However, when gender preference was compared, this study showed that male youths preferred English while the female youths preferred to use Malayalam. Among the reasons forwarded by the youths for preferring English was that Malayalam was not being offered in schools and it was not used beyond the domains of family and home. In addition, their parents did not teach Malayalam to them nor emphasised the importance of this language. To these youths, English was considered to be more important than Malayalam in their daily life for communication and in particular for a better career prospect. This study hopes the findings have shed some light on the English usage among Malayalee youths as well as the choice of language of the different genders and the identity markers of Malayalee youths in this particular study.